КОМУТУЮЧА НАПРУГА ТРИФАЗНОГО ДВОМОСТОВОГО КОМПЕНСАЦІЙНОГО ПЕРЕТВОРЮВАЧА - Бойко, В.C. (Інститут електродинаміки НАН України, Київ, 2024)
The results of a study of electromagnetic processes in a three-phase two-bridge compensation converter, which is one of the options for the circuit implementation of new generation compensation converters, are presented. The commutating link of the converter contains a three-phase capacitor battery and a three-phase group of fully controlled devices. This technical solution makes it possible to make the process of recharging capacitors controllable. Moreover, it becomes possible to change not only the magnitude of the capacitor voltage, but also its shape. It was noted that in the previous generation of compensation converters there was no ability to change the shape of the commutating voltage. The latter is a significant advantage of new generation devices, since it allows for high energy characteristics of the converter. This is confirmed by the results of a study of the energy capabilities of the converter under study in nine operating modes presented in the publication and the conclusion on the most effective modes. References 9, figures 10.